ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMAHAMAN MASYARAKAT DESA BENTENG RENDAH TERHADAP PRODUK PERBANKAN SYARIAH - Wina Sari Asmara; Raden Hebat Kurnia; Iswanto Iswanto (JOURNAL SAINS STUDENT RESEARCH, 2025)
Sharia Banks are banks that carry out their business activities based on Sharia principles and according to their type consist of Sharia Commercial Banks, Sharia Business Units and Sharia People's Financing Banks (BPRS). Judging from the development side, sharia banks are currently not lagging behind with progress like conventional banks, but there is still one of the problems faced by sharia banks is the low level of public understanding of sharia banking products, especially caused by the dominance of conventional banking so that sharia banking is still underestimated by some people, based on a survey conducted by researchers in Benteng Bawah Village, which is quite large and the majority of the population is Muslim, however their understanding of sharia banking products is very poor, from the results of pre-research conducted by researchers in the field, this is the weakness of the Benteng Bawah Village Community in understanding bank products. sharia, namely lack of knowledge about sharia banks, lack of information relating to sharia bank products, socialization carried out by sharia banks is not optimal, especially socialization for rural communities, and lack of community experience in carrying out financing or other transactions with sharia banks.